Vice patrol: cops, courts, and the struggle over urban gay life before Stonewall - Lvovsky, Anna (The University of Chicago Press, 2021)
"Vice Patrol: Cops, Courts, and the Struggle over Urban Gay Life chronicles how local police and criminal justice systems intruded on gay individuals, criminalizing, profiling, surveilling, and prosecuting them from the 1930's through the 1960's. Anna Lvovsky details the progression of enforcement strategies through the targeting of gay-friendly bars by liquor boards, enticement of sexual overtures by plainclothes police decoys, and surveilling of public bathrooms via peepholes and two-way mirrors to catch someone "in the act." Lvovsky shows how the use of tactics indistinguishable from entrapment to criminalize homosexual men in public and private spaces produced charges brought forward and disputed by attorneys and evidence that had to stand before judges, who at times intervened against punitive policies. In Vice Patrol the author demonstrates how developments in the psychological, medical, and sociological handling of homosexuality filtered into police stations, courthouses, and the wider culture"--